Military Acronyms: Notion, Categorization and Classification - Bloshchynskyi, Ihor; Lemeshko, Olha; Hlukhmaniuk, Oleh; Kalyniuk, Nataliia; Lemeshko, Volodymyr; Moroz, Nadiia; Pavliuk, Tetiana; Shchegoleva, Tatyana; Bets, Iryna; Nazarenko, Nataliia; Sinkevych, Serhii (Forum for Linguistic Studies, 2025)
The article presents an overview of acronyms classification in English military terminology. Legal documents, official website of State Border Guard Service of Ukraine, journals and dictionaries related to military terminology were investigated in the research. Mostly used acronyms in English military terminology were classified and 718 definitions were singled out. Such methods as theoretical analysis, comparison, substantiation, and generalization, systematization of theoretical and practical material were used for the analysis of the scientific sources concerning military acronyms, comparing the military terminology acronyms according to their common usage, the selection of acronyms groups and their categorization correspondingly. As a result, the acronyms were divided according to their common usage into the following groups and subgroups: management acronyms (personnel, positions and organization acronyms), service acronyms (NATO and everyday activity acronyms), military operations acronyms (operational and communication acronyms), armament and military equipment acronyms (military equipment, weapons and ammunition acronyms), military medicine acronyms (medical training and medical terms acronyms), military law acronyms (documents, personnel and legal bodies’ acronyms), vehicles acronyms (marine vessels, land vehicles and military aircraft acronyms), nuclear area acronyms (missile, nuclear legislation and nuclear bodies acronyms), Armed forces organization acronyms (Army Command, Air Force, Navy and military intelligence acronyms). At the final stage of the study military terminology acronyms classification was developed and graphically presented using the MindManager program to categorize military acronyms according to their common usage.